Dual role of reactive oxygen species in autophagy and apoptosis induced by compound PN in prostate cancer cells - Choi, Hyeun Deok; Kim, Kwang-Youn; Park, Kwang Il; Kim, Sang-Hun; Park, Sul-Gi; Yu, Sun-Nyoung; Kim, Young-Woo; Kim, Dong Seob; Chung, Kyung Tae; Ahn, Soon-Cheol (Molecular & cellular toxicology, 2021)
Background Pharbitis nil (L.) Choisy (PN) is used as a traditional herb in East Asia and exhibits anti-parasitic, purgative, diuretic, anti-inflammatory, and anti-cancer activities. However, the molecular mechanisms underlying the anti-cancer activity are not well understood. Objective This study aims to elucidate the effects of reactive oxygen species (ROS), generated after treatment with the compound PN, on the induction of apoptosis and autophagy, which are pathways that underly the mechanisms of cell death and cell survival in human prostate cancer cells. Results The MTT assay and western blot analysis were used to assess the effects of compound PN on cell viability and the expression of apoptosis- and autophagy-related proteins in prostate cancer PC-3 cells. The effects of PN on apoptosis (via annexin V/propidium iodide staining), autophagy (via acridine orange staining), and ROS (via DCFH-DA staining) were investigated using flow cytometry. Compound PN induced the production of intracellular and mitochondrial ROS leading to increased apoptosis and autophagy in PC-3 cells. Interestingly, pretreatment with N -acetyl- l -cysteine (NAC), an intracellular ROS scavenger, enhanced compound PN-induced apoptosis, but reduced levels of autophagy. In contrast, pretreatment with diphenyleneiodonium (DPI), an inhibitor of mitochondrial ROS, reduced compound PN-induced apoptosis and enhanced autophagy. Inhibition of autophagy led to acceleration of apoptosis in a PN-induced ROS-dependent manner. Compound PN-induced ROS production from two different sources, an intracellular source and mitochondrial source. ROS production in these differing locations had different effects on apoptosis and autophagy. They acted either by promoting cell death or cell survival through regulating autophagy to either escape or enhance apoptotic cell death. Conclusion This crosstalk between ROS-activated signals in apoptosis and autophagy induction by PN provides new insights into the molecular mechanisms of this compound and suggests that PN may be a potential therapy for prostate cancer treatment.